European Perspectives: The European Transport and Environment Reporting Mechanism (TERM) - Stead, Dominic (European Journal of Transport and Infrastructure Research, 2003)
This new regular section looks at emerging issues with a definite pan-European focus and high significance for transport and/or infrastructure research. Three general inter-related themes will be examined in the new section − policy , practice and research . The connections between these themes will also be the focus of the section. Sometimes the section will primarily address one of these themes and at other times it will address two or all three of the themes. The policy theme will include recent developments in European transport policy and also recent developments in environmental, regional development and economic policy where there are specific implications for transport. The practice theme will include issues such as European benchmarking and pilot projects as well as recent developments in different transport industries across Europe (shipping, aviation and rail for example) and prospects for the future. The research theme will include topics such as recent developments in European research priorities and funding opportunities for transport and/or infrastructure research.